The International Rugby Board (IRB) Pitch Side Concussion Assessment trial: a pilot test accuracy study. Issue 8 (4th July 2014) - Fuller, Gordon Ward; Kemp, Simon P T; Decq, Philippe
Abstract : Background: 'On the field and on the run' assessments of head impact events in professional rugby have resulted in a high proportion of players subsequently diagnosed with confirmed concussion not leaving the field of play at the time of injury. The International Rugby Board (IRB) consequently developed a process to support team doctors in the recognition and management of players at risk of concussion, including development of a multimodal assessment instrument—the Pitch Side Concussion Assessment (PSCA) tool. Methods: This was a pilot cohort study designed to determine the feasibility of assessing the accuracy of the IRB PSCA tool in elite male rugby. The study population comprised consecutive players identified with a head impact event with the potential to result in concussion during eight international/national competitions. Players were assessed off field by match-day or team doctors, following a temporary substitution. The accuracy of the PSCA tool was measured against a reference standard of postmatch confirmed concussion, based on clinical judgement aided by an established concussion support instrument. Results: A total of 165 head injury events with the potential to cause concussion were included in the study. The PSCA tool demonstrated a sensitivity of 84.6% (95% CI 73.5% to 92.4%) and a specificity of 74% (95% CI 64.3% to 82.3%) to identify players subsequently diagnosed with confirmed concussion. The negative predictive value was 88.1% (95% CI 79.2% to 94.1%); the positive predictive value was 67.9% (95% CI 56.6% to 77.8%). There were no major barriers identified that would prevent the evaluation of the PSCA process or tool in a future large-scale study. Conclusions: This pilot study has provided the first preliminary estimates for the performance of the PSCA tool, suggesting a potentially favourable balance between positive and negative predictive values. The study has also offered a strong basis to conduct a further larger trial, providing information for sample size calculations and highlighting areas for methodological development.